Aplicação de silício em arroz de terras altas irrigado por aspersão - dos Reis, Marcos Aguiar [UNESP]; Arf, Orivaldo [UNESP]; da Silva, Matheus Gustavo [UNESP]; de Sá, Marco Eustáquio [UNESP]; Buzetti, Salatiér [UNESP] (My University, 2008)
The use of chemical elements considered as beneficial to crops has become common among farmers. The silicon case is interesting, since despite not being essential physiologically for rice crop, it demonstrates that through its absorption it promotes benefits. Therefore, this experiment aimed to evaluate the effect of doses of SiO2 (0, 150, 300, 450, 600, 750 and 900 kg ha-1) at seed sowing time, in two upland rice cultivars (IAC 201 and IAC 202), under sprinkler irrigation, during the agricultural years of 2002/03 and 2003/04 in Selvíria, Mato Grosso do Sul State, Brazil. The cultivar IAC 202 can present higher yield than IAC 201, with similar industrial quality and lower laying index. Silicon applications were not sufficient to reduce laying index of IAC 201. In general, silicon application does not interfere in grain productivity and industrial yield of the cultivars used.
Silicon application in upland rice under sprinkler irrigation
Keywords: Cultivar; Oryza sativa L; Silicon doses